Reimagining and Recalibrating Information Studies: iSchools, the Way Forward - Urs, Shalini R. (Journal of Information and Knowledge, 2023)
Reviews the various definitions of information and proposes that it has a physical, linguistic and cognitive manifestations. The changing landscape of information studies and the factors that contributing to this are examined. The origins and development of library education in USA, UK and India are briefly mentioned. The changing nature of the information profession in terms of the various job titles that information professionals can fit into is reviewed. Briefly reviews the i-school movement, and suggests that i-schools are the way forward.